Characterization of mind wandering using fNIRS - Durantin, Gautier; Dehais, Frederic; Delorme, Arnaud (Frontiers in Systems Neuroscience, 2015)
Assessing whether someone is attending to a task has become important for educational and professional applications. Such attentional drifts are usually termed mind wandering. The purpose of the current study is to test to what extent a recent neural imaging modality can be used to detect mind wandering episodes. Functional near infra-red spectroscopy is a non-invasive neuro-imaging technique that has never been studied so far to measure mind wandering. The Sustained Attention to Response Task was used to assess when subjects attention leaves a primary task. 16-channel fNIRS data were collected over frontal cortices. We observed significant activations over the medial prefrontal cortex during mind wandering, a brain region associated with the default mode network. fNIRS data were used to classify mind wandering data above chance level. In line with previous brain-imaging studies of mind wandering, our results confirm the ability of fNIRS to detect Default Network activations in the context of mind wandering.